The Translation of Lexical Modal (Insist) in English Modality and its Equivalents in Indonesian Language: Syntactic and Semantic Studies - Novan Setiawan Nugraha, Deden; Solihin, Ismail; Ramadhan, Nabilah; Silviani Marinda, Vina (International Journal of Psychosocial Rehabilitation, 2020)
Translation always involves two languages, so a translator must realize that every language system is not the same. One of the differences that exists in every language system is the grammatical category, and one of the grammatical categories that must be considered by an interpreter is the modality system. This modality system has a disclosure, which is called a disclosure modality. Expressed modality is a term used for words, phrases, or clauses that express the speakers' commitment or belief in a proposition. By using the descriptive method, this research describes the lexical modal (insist) in English modality and Indonesian based on its meaning. The data was taken from corpus linguistics, that is, the Corpus of Contemporary American English (COCA).